Task-ambient lighting: a sustainable design method investigation - Caton, Nicholas A (Kansas State University, 2007)
Today's engineers of building lighting systems must maintain a careful balance between the demands of accepted standards of practice, the necessity of life safety, the system performance needs of the client, and the developing national energy standards and certifications gaining prominence in the public eye. These sources of influence on the design process can create conflicts between the pressing need to conserve system energy usage and a costlier and perhaps unacceptable end-result for the client. In this climate, various governmental organizations and industry cooperatives have been funding published research and case-studies in order to promote sustainable design practices. Within these publications are repeated references to a "Task-Ambient" lighting fixture layout strategy. Multiple recent publications cite profound energy-saving benefits attainable using this design method. However, there is a noticeable lack of measured data concerning other qualities of this layout scheme, such as the end-user's comfort and ability to perform tasks under the resulting light distributions. Whether this lack of data resulted from the added complexity associated with such non-numerical measurements, or for some other unknown reason, this report explores this gap in the available data. An extended survey procedure was developed to approach the problem of measuring these unknown qualities of the Task-Ambient design strategy. This involved constructing multiple physical lighting layout mockups, defining the features of the Task-Ambient strategy which necessitated measurement, and designing objective tasks tailored to measure each of these non-numerical qualities. The careful analysis of this study's data results yields trends indicative of the Task-Ambient strategy, relative to a standard uniform layout, adversely affecting productivity, concentration, and the participants' subjective perceptions of the space's light distribution. The lowered level of energy use was however affirmed. The implications of these results are that the Task-Ambient strategy, while an efficient method of lighting system layout design, may not be beneficial for the client in other respects.
Keywords: Task-ambient; Lighting; Task; Ambient; Layout; Method; Architecture (0729); Energy (0791); Engineering, Electronics and Electrical (0544)